1985
DOI: 10.1002/1097-0142(19850101)55:1<108::aid-cncr2820550118>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Minor salivary gland tumors. A histologic and immunohistochemical study

Abstract: Clinical, histologic, and immunohistochemical data were reviewed and evaluated on 238 oral minor salivary gland tumors. Benign neoplasms accounted for 65% of the total. Pleomorphic adenomas were the most common of all neoplasms, and mucoepidermoid carcinomas were the most frequently encountered malignancies. Pleomorphic adenomas and adenoid cystic carcinomas stained positive for S‐100 protein. Immunohistochemistry was believed to be of potential assistance in diagnosis of salivary gland tumors and in predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
1
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 13 publications
12
61
1
2
Order By: Relevance
“…Based on the findings in this series and those reported earlier, this tumor is a luminal epithelial lineage. The tumor cells show a strong reaction with epithelial markers, including AE1/ AE3, CK7, CAM5.2, CK903, EMA, and CK19; reactions with CK8 and CK13 are also reported [14,15,21,29,40,79,98,99]. Further, the neoplastic cells are strongly and diffusely reactive with S100 protein [14,100], despite earlier reports of negative reactions [40,79].…”
Section: Immunohistochemical Studiessupporting
confidence: 63%
See 2 more Smart Citations
“…Based on the findings in this series and those reported earlier, this tumor is a luminal epithelial lineage. The tumor cells show a strong reaction with epithelial markers, including AE1/ AE3, CK7, CAM5.2, CK903, EMA, and CK19; reactions with CK8 and CK13 are also reported [14,15,21,29,40,79,98,99]. Further, the neoplastic cells are strongly and diffusely reactive with S100 protein [14,100], despite earlier reports of negative reactions [40,79].…”
Section: Immunohistochemical Studiessupporting
confidence: 63%
“…Several studies were excluded if no specific or separable information was given about CanAd or if the illustrations were not characteristic [23,51,55,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Several of the cases seemed to have been included multiple times in different series reports [9,10,40,[79][80][81][82][83].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Chaudhry et al 1961;Eneroth 1971;Eneroth and Hjertman 1972;Isacsson and Shear 1983;Eveson and Cawson 1985a, b ;Regezi et al 1985) have documented the distribution of series of minor salivary gland tumors seen in some countries. Reports from various parts of the world indicate that there are differences in the frequency of particular histologic types and in the frequency with which minor salivary glands are involved.…”
Section: )mentioning
confidence: 99%
“…However , myoepithe- lial cells surrounding acini and intercalated ducts were specifically positive for S-100 protein [19][20][21]. On the other hand, NAKAZATO et al [12] and ERLANDSON et al [22] demonstrated that acini cells were S-100 protein-positive in some of the cases they examined, and other reports also described S-100 protein immunoreactivity in intercalated ducts [11,12,14,18,19]. The variation in findings among these studies may be ascribed to the differing sensitivities of the immunoperoxidase methodologies employed by various laboratories, different primary antibody sources, poor specimen fixation and differences in sample size [18,19].…”
Section: Solid Epithelial Areasmentioning
confidence: 99%